Village modernization may contribute more to farmland bird declines than agricultural intensification. Issue 6 (24th October 2021) - Rosin, Zuzanna M.; Pärt, Tomas; Low, Matthew; Kotowska, Dorota; Tobolka, Marcin; Szymański, Paweł; Hiron, Matthew
Abstract: The central tenet of European farmland ecology is that agricultural intensification during the 20th century was largely responsible for dramatic declines in species abundances. However, during this time, human rural settlements were also undergoing radical changes through modernization, with undocumented biodiversity impacts in this important wildlife habitat. We performed the first ever large‐scale study to disentangle the impact of these simultaneous processes on farmland bird diversity in 104 Polish villages. We show that modernized villages and their surrounding agricultural fields had 50–60% fewer birds than those in and around comparable older villages. The relative contribution of modernization versus agricultural intensification to predicted bird declines was 88% versus 12% for bird communities in villages and 56% versus 44% in surrounding croplands, with considerable variation among ecological species subgroups. These results challenge our current understanding of agricultural ecosystem ecology and how best to implement conservation measures costing billions of euros annually.